54. We need to find the value of the expression
![(1)/(12^(-1))](https://img.qammunity.org/2023/formulas/mathematics/college/8nen3uy0hkozcd062fnq525j6kuddz9osz.png)
In order to do so, we can use the following definition for exponentials:
![\begin{gathered} x^(-1)=(1)/(x) \\ \\ (1)/(x^(-1))=\frac{1}{\frac{1}{x^{}}}=1\cdot(x)/(1)=x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/p4sysid9rmmckeyjxnnbpbv6s74m3932wl.png)
In this problem, we have x = 12. Thus, we can evaluate the expression as follows:
![(1)/(12^(-1))=12](https://img.qammunity.org/2023/formulas/mathematics/college/v583y4fnmemjw8f6vw6r4aikdy6v5vgagu.png)
Let's see another way to find the same result.
Notice that when a number has the positive exponent n, it means that we have a product of n factors of that number. For example:
![\begin{gathered} 2^3=2\cdot2\cdot2=8 \\ \\ 2^1=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zy7nvyaajllyzbi3kb6te6idjovx3oas3g.png)
On the other hand, when the exponent is negative, by definition, the minus sign tells us to find the inverse of that number. For example:
![\begin{gathered} 2^(-3)=\mleft((1)/(2)\mright)^3=\mleft((1)/(2)\mright)\cdot\mleft((1)/(2)\mright)\cdot\mleft((1)/(2)\mright)\text{ because }(1)/(2)\text{ is the inverse of }2 \\ \\ 2^(-1)=(1)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ch2bret0nqojvf3gvhkbxwrd66qkqwbr72.png)
Also, notice that 1 to any exponent equals 1. For example:
![\begin{gathered} 1^0=1 \\ 1^1=1 \\ 1^2=1 \\ 1^(-1)=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o0bwjpkxwjzprpeyva80x8lxo4w0katqc9.png)
So, we can write:
![(1)/(12^(-1))=(1^(-1))/(12^(-1))=\mleft((1)/(12)\mright)^(-1)=\mleft((12)/(1)\mright)=12](https://img.qammunity.org/2023/formulas/mathematics/college/bnasrd0cfvuq0wy73wl1u3hog6sepz9fa6.png)
Therefore, the value of the given expression is 12.